2001
DOI: 10.1083/jcb.200102086
|View full text |Cite
|
Sign up to set email alerts
|

Sodium channel β1 and β3 subunits associate with neurofascin through their extracellular immunoglobulin-like domain

Abstract: Sequence homology predicts that the extracellular domain of the sodium channel β1 subunit forms an immunoglobulin (Ig) fold and functions as a cell adhesion molecule. We show here that β1 subunits associate with neurofascin, a neuronal cell adhesion molecule that plays a key role in the assembly of nodes of Ranvier. The first Ig-like domain and second fibronectin type III–like domain of neurofascin mediate the interaction with the extracellular Ig-like domain of β1, confirming the proposed function of this dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
145
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(148 citation statements)
references
References 33 publications
(59 reference statements)
3
145
0
Order By: Relevance
“…A polyclonal anti-␤3 antibody was a gift from Dr. William A. Catterall (University of Washington, Seattle, WA) and has been described previously (20). Cy3-conjugated anti-human-Fc antibodies were obtained from Jackson ImmunoResearch Laboratories (West Grove, PA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A polyclonal anti-␤3 antibody was a gift from Dr. William A. Catterall (University of Washington, Seattle, WA) and has been described previously (20). Cy3-conjugated anti-human-Fc antibodies were obtained from Jackson ImmunoResearch Laboratories (West Grove, PA).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that Nf186 is important for determining node of Ranvier location (2, 18). Ratcliffe et al (20) showed that the extracellular domain of ␤1 interacts with Nf186 in a heterologous system using coimmunoprecipitation techniques. As shown in Fig.…”
Section: ␤1 Interacts With the Fibronectin-like Domains Of Contactin-mentioning
confidence: 99%
See 1 more Smart Citation
“…Auxiliary ␤-subunits affect the assembly, trafficking, and electrophysiological activities of ␣-subunits (6) and have recently been shown to link sodium channels to extracellular matrix proteins via their association with neurofascin (7). The neuronal adhesion molecule contactin/F3 increases the membrane insertion of sodium channels by direct (8) or indirect (9) association with the ␣-subunit of the channels.…”
mentioning
confidence: 99%
“…They comprise a single Sodium channel auxiliary subunits, Na 1 to Na 4, interact with the different subunits and alter their physiological properties and V β V β α subcellular localization. These proteins have a single transmembrane segment, a large N-terminal extracellular domain that is homologous in structure to a variable chain (V-type) immunoglobulin-like fold, and a short C-terminal intracellular segment ( ) ( with an extracellular Ig-fold, they also serve as cell adhesion molecules by interacting with extracellular matrix proteins, cell adhesion molecules, and cytoskeletal linker proteins ( ; ; ; Ratcliffe et al, 2000Srinivasan et al, 1998Ratcliffe et al, 2001 ). The Na subunits are a recent evolutionary addition to the family of ion channel associated proteins, as Malhotra et al, 2002 V β they have only been identified in vertebrates.…”
Section: Voltage-gated Sodium Channelsmentioning
confidence: 99%